Reaching Generation Z: TikTok as a Police Communication Tool in the Field of Promoting Employment - Kovačič, Anita (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
In the paper, we discuss the use of the social network TikTok as a communication tool of the Slovenian police in the field of employment promotion. The Slovenian police also direct their communication approaches towards addressing Generation Z. Consequently, we address the characteristics of members of this generation, their career preferences and expectations. TikTok, where Generation Z spends more and more time, is also used for this purpose by foreign institutions of the wider public sector. In the paper, we present the approaches of the Slovenian police, which, with the help of humour, an extremely effective way of addressing the public, and authentic content, address the specificity of the police profession. Concrete experiences in this area and approaches that have been recognised by the professional public in the field of strategic communication and awarded both nationally and internationally are presented.